Theoretical and experimental research on the micro interface lubrication regime of water lubricated bearing. (April 2021) - Xie, Zhongliang; Zhang, Yun; Zhou, Jinzhu; Zhu, Weidong
Highlights: The fluid flow characteristics inside the micro cavities are obtained. Effects of operating conditions and structural parameters on the fluid features are investigated. The lubrication mechanisms of the micro interface are elaborated. Abstract: The paper aims to reveal the micro interface lubrication regimes of water lubricated bearing. Typical micro cavities are explored through computational fluid dynamic analysis. Streamline, pressure, eddy viscosity and kinetic energy distribution are obtained in the micro cavities. Influences of operating conditions and dimensionless structural parameters on fluid features are explored with detailed information. Velocity vectors as well as pressure contours are acquired inside the cavity. Analysis elaborates the micro interface lubrication mechanisms as well as the changing rules of lubrication performances with structural parameters for the cavity. Experimental data verifies the correctness of the lubrication model and the lubrication regimes. The micro interface lubrication mechanisms are revealed and they apply to bearings with different dimensions. Research results lay solid foundation for further optimal design of surface topography of such bearings.